Habib Husein Jafar Al-Hadars Da'wa Content Commodification on Youtube - Akhmad Roja Badrus Zaman; Mahin Muqaddam Assarwani (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2021)
Advances in technology and information provide new opportunities for preachers to be able to take part in spreading Islamic teachings through various social media platforms. One of the preachers who took the role to preach through social media was Habib Husein Jafar al-Hadar. This article examines Habib Husein Jafars missionary activities on the social media platform he uses, Youtube. The researcher analyzes the data by observing virtually and visually (virtual ethnography) on the dakwa content displayed by Habib Husein Jafar through Youtube. The study shows that: 1) the attention to the spiritual enlightenment efforts of the younger generation is the basis of the selection of the social media platform Youtube - because based on previous research, the users of this social media platform are 18-29 years of age; 2) starting from the dakwa consumers who are primarily young people, the content they present is suitable to their needs and lifestyle and 3) by using the concept of the circuit of culture analysis, Habib Husein Jafar in various ranges can reconstruct people's perception of ones definition of holiness. It is not limited based on normative appearance - cloaked and sacrificed, for example - but more on the substantive side, namely by behaving and having knowledgeable skills. With the variety of content, he could visualize himself as a pious young man by not abandoning his social status as a young person.